Herpes Simplex Virus 1 Open Reading Frames O and P Are Not Necessary for Establishment of Latent Infection in Mice - Randall, Glenn (American Society for Microbiology, 2000)
Open reading frame (ORF) O and ORF P partially overlap and are located antisense to the γ(1)34.5 gene within the domain transcribed during latency. In wild-type virus-infected cells, ORF O and ORF P are completely repressed during productive infection by ICP4, the major viral transcriptional activator/repressor. In cells infected with a mutant in which ORF P was derepressed there was a significant delay in the appearance of the viral α-regulatory proteins ICP0 and ICP22. The ORF O protein binds to and inhibits ICP4 binding to its cognate DNA site in vitro. These characteristics suggested a role for ORF O and ORF P in the establishment of latency. To test this hypothesis, two recombinant viruses were constructed. In the first, R7538(P−/O−), the ORF P initiator methionine codon, which also serves as the initiator methionine codon for ORF O, was replaced and a diagnostic restriction endonuclease was introduced upstream. In the second, R7543(P−/O−)R, the mutations were repaired to restore the wild-type virus sequences. We report the following. (i) The R7538(P−/O−) mutant failed to express ORF O and ORF P proteins but expressed a wild-type γ(1)34.5 protein. (ii) R7538(P−/O−) yields were similar to that of the wild type following infection of cell culture or following infection of mice by intracerebral or ocular routes. (iii) R7538(P−/O−) virus reactivated from latency following explanation and cocultivation of murine trigeminal ganglia with Vero cells at a frequency similar to that of the wild type, herpes simplex virus 1(F). (iv) The amount of latent R7538(P−/O−) virus as assayed by quantitative PCR is eightfold less than that of the repair virus. The repaired virus could not be differentiated from the wild-type parent in any of the assays done in this study. We conclude that ORF O and ORF P are not essential for the establishment of latency in mice but may play a role in determining the quantity of latent virus maintained in sensory neurons.